Tantangan Hukum dalam Pengaturan Jaminan Keselamatan Pasien Home Care Digital bagi Lansia dan Penderita Penyakit Kronis - Davisa Yuly Aghnia; Isharyanto Isharyanto (Universitas Sebelas Maret, 2026)
The concept of home healthcare through digital home care services represents a strategic innovation in the development of the Indonesian healthcare system. This service offers an effective solution to improve the comfort and continuity of care for elderly patients and patients with chronic diseases, who are vulnerable groups. However, integrating digital technology into healthcare services raises legal challenges, particularly regarding the regulation of patient safety guarantees. This study aims to analyze the legal challenges that regulate mechanisms of accountability and risk prevention in the safety of elderly and chronically ill patients receiving Digital Home Care in Indonesia, with a focus on legal protection. The method used is a deductive, interpretive legal approach, grounded in a normative analysis of laws and regulations, relevant literature, and several case studies. The results show that the legal challenges in implementing Digital Home Care primarily concern providing effective legal protection for elderly patients and those with chronic diseases, without compromising service quality standards or patient safety principles. The required oversight framework is not sufficient to fulfill only administrative requirements; it must also encompass professional responsibility, ethical compliance, and criminal liability in the event of negligence that causes harm. Therefore, regulatory updates are needed to strengthen oversight and emphasize service providers' legal accountability, ensuring they remain aligned and adaptable to technological advances. This research is expected to make a real contribution by encouraging the development of adaptive, comprehensive legal policies to protect vulnerable patient groups in the digital era, especially in the context of digital home care services.